2003
DOI: 10.1002/jcu.10195
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic evaluation of the anterior liver surface in chronic liver diseases using a 7.5‐MHz annular‐array transducer: Correlation with laparoscopic and histopathologic findings

Abstract: Our results suggest that sonographic evaluation of the liver surface with a 7.5-MHz annular-array transducer using this classification provides detailed information on the evolution of chronic liver diseases that correlates with the laparoscopic and histopathologic findings and thus is a useful noninvasive method for monitoring the disease course to cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…During examination LLS was scored as smooth, irregular, or nodular. As per previously published data [11,13], LLS was considered to exclude cirrhosis if smooth, indeterminate if irregular, and diagnostic of cirrhosis if nodular. Three representative images were recorded.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…During examination LLS was scored as smooth, irregular, or nodular. As per previously published data [11,13], LLS was considered to exclude cirrhosis if smooth, indeterminate if irregular, and diagnostic of cirrhosis if nodular. Three representative images were recorded.…”
Section: Patientsmentioning
confidence: 99%
“…Among ultrasonographic signs of cirrhosis, liver surface nodularity, evaluated by high-resolution ultrasound at the left liver lobe (LLS), is the most accurate [11][12][13][14]. Since the main limitation of the technique is its operator dependency [11], it is possible that an objective method to measure LLS may increase its accuracy and applicability.…”
Section: Introductionmentioning
confidence: 99%
“…Another important aspect of the paper is the confirmation that TE is not a good method to obviate the need of endoscopy to screen for varices in patients with TE values above the cirrhosis threshold or higher cut-offs [13,14]. This is not surprising since despite an increased portal pressure being a requirement for the formation of varices [6], in itself the magnitude of the portal pressure elevation does not correlate with either the presence or size of varices.…”
Section: See Article Pages 59-68mentioning
confidence: 88%
“…A number of studies even showed that diagnosis of cirrhosis was more reliable by peritoneoscopy than by liver biopsy, since the latter may not demonstrate cirrhosis in an unequivocally cirrhotic liver, due to the small size of liver tissue obtained by needle biopsy [2,4]. Current imaging techniques have such a resolution that it is hard to believe that they can not show a nodular liver surface [13]. Even very simple techniques, like ultrasonography using a high frequency transducer have a very high resolution and should allow observation of nodules on the liver surface (Fig.…”
Section: See Article Pages 59-68mentioning
confidence: 94%
“…Liver border assessment is a simple technique that provides a high positive predictive value (PPV) and should therefore be accurate in identifying patients with a high probability of advanced fibrosis or cirrhosis while avoiding the risks of liver biopsy. In general, false negative results derive from micronodular cirrhosis, use of low-frequency transducers, and explorer subjectivity, whereas false positive results are due to liver tumors or diffuse nodular hyperplasia (16)(17)(18)(19)(20). Berzigotti et al have recently demonstrated that the use of high-frequency transducers together with the objective measurement of 2-cm linear segment on the surface of the liver's left lobe may reduce the number of uncertain cases (irregular borders) and increase accuracy and reproducibility (21).…”
mentioning
confidence: 99%